The Influence of Saturated Fat, Cholesterol, Corn Oil and Linseed Oil on the ADP-Indueed Platelet Adhesiveness in the Rat - Nordöy, Arne (Thrombosis and Haemostasis, 1965)
1. The ADP induced platelet adhesiveness was tested in platelet rich plasma from rats on a normal diet, on a saturated fat and cholesterol diet and on this last diet supplemented with corn oil or linseed oil.2. An increased platelet adhesiveness was present in animals given a saturated fat and cholesterol diet. Addition of corn oil to this diet further increased the adhesiveness, whereas addition of linseed oil normalized the platelet adhesiveness.3. The relation between the ADP induced platelet adhesiveness tested in vitro and the tendency to thrombosis is discussed.